Escalating UMKM Binaan Rumah Kreatif Sleman melalui Strategi Pemasaran dan Media Digital - Rullyana Puspitaningrum Mamengko (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The results of the author's visit to the Rumah Kreatif Sleman (RKS) resulted in the initiation of collaboration between Universitas Negeri Yogyakarta and RKS. This collaboration is expected to improve the capabilities and skills of the MSME owners assisted by RKS in developing their businesses. From the results of interviews with RKS managers, it is known that there are still weaknesses of MSMEs in terms of consistency and maturity in planning marketing strategies that are oriented towards achieving maximum revenue and profit. In addition, these MSMEs are also still weak in terms of strategy and consistency in marketing through digital media. For this reason, the author provides training as a form of community service activity for MSMEs assisted by RKS through mastery revenue and marketing strategies using digital media. The service method carried out starts from the collaboration stage, the preparation stage, the activity implementation stage, and the evaluation stage. Evaluation is carried out in 2 (two) stages, namely (1) evaluation of activities, when training activities are carried out; and (2) final evaluation, at the end of the implementation of activities. MSMEs